Monofilament test and Ankle Brachial Index examination as early detection of Peripheral Arterial Disease at the Makassar City Health Center - Syaiful; Risnawati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
The increase in the number of diabetics is influenced by factors of age, overweight, ignorance and unhealthy lifestyles. The most common complication is diabetic foot ulcer with an incidence rate of 15%. Some things that need to be considered in everyday life to prevent diabetic foot injuries are diet (nutritional therapy), exercise (exercise), pharmacological therapy, and education. The purpose of this study was to detect early the incidence of neuropathy using the monofilament test and the incidence of peripheral arterial disease using ABI. The research method used was descriptive research with a quantitative approach, descriptive research was used to assess the incidence of Peripheral Arterial Disease cases using the Monofilament Test and ABI (Ankle Brachial Index) examination, with a total of 50 respondents with diabetes mellitus. The results showed that 47 respondents (94%) at the time of the monofilament test showed normal results or did not experience neuropathy, while there was 1 respondent who was included in the category of suspected neuropathy, and there were 2 respondents or around 4% who had been detected suffering from neuropathy. The results of the Ancle Brachial Index examination showed that 8 respondents or around 16% were identified as having Peripheral Arterial Disease, and 42 respondents or around 84% were not detected as having Peripheral Arterial Disease. The conclusion is the low number of people with neuropathy and Peripheral arterial disease because DM sufferers have a DM exercise routine 2x a week, this will help improve blood flow and prevent an increase in blood glucose level.